2019
DOI: 10.1029/2018wr023403
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Snowpack Simulations—Assessing the Impact of Model Structure, Parameter Choice, and Forcing Data Error on Point‐Scale Energy Balance Snow Model Performance

Abstract: In this study, we assess the impact of forcing data errors, model structure, and parameter choices on 1‐D snow simulations simultaneously within a global variance‐based sensitivity analysis framework. This approach allows inclusion of interaction effects, drawing a more representative picture of the resulting sensitivities. We utilize all combinations of a multiphysics snowpack model to mirror the influence of model structure. Uncertainty ranges of model parameters and input data are extracted from the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 55 publications
12
110
0
Order By: Relevance
“…We evaluated the snow model parameter sensitivity for the full winter season from 2007 to 2013. As suggested by Günther et al (2019) through model sensitivity analyses conducted for a snow monitoring station in the Northern Calcareous Alps (Tyrol, Austria), snow albedo parameters exhibited higher sensitivity during the melt season than the accumulation season. In this regard, future sensitivity evaluations could be performed separately for the accumulation and melt period to better understand the parameter behaviors and their implications for snow processes.…”
Section: Future Workmentioning
confidence: 86%
“…We evaluated the snow model parameter sensitivity for the full winter season from 2007 to 2013. As suggested by Günther et al (2019) through model sensitivity analyses conducted for a snow monitoring station in the Northern Calcareous Alps (Tyrol, Austria), snow albedo parameters exhibited higher sensitivity during the melt season than the accumulation season. In this regard, future sensitivity evaluations could be performed separately for the accumulation and melt period to better understand the parameter behaviors and their implications for snow processes.…”
Section: Future Workmentioning
confidence: 86%
“…The avalanche forecasting services of some countries use a chain composed of meteorological forcings, coming from either a Numerical Weather Prediction model (NWP) or observations, and a detailed multilayer snowpack model such as Crocus (Vionnet et al, 2012) or SNOWPACK (Lehning et al, 2002). Both meteorological forcings and snowpack modelling induce errors and uncertainties in the simulations (Essery et al, 2013;Vernay et al, 2015;Raleigh et al, 2015;Günther et al, 2019). These errors are considerably limiting the use of snowpack models by avalanche hazard forecasters (Morin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ground heat flux, which was not considered in this study, has been shown to provide less than 1% of total energy input and is thus of minor importance during RoS events (Würzer et al, ). Finally, it should be noted that the application of physically based snow energy balance models is found to be sensitive to the parameter choice, the model structure, and the forcing error, even when applied at the point scale (Günther et al, ). An application of such approaches at the catchment scale is further hampered by the high temporal and spatial variability of input variables and the lack of corresponding measurements at this scale.…”
Section: Discussionmentioning
confidence: 99%